Risk Factors for The Incident of Hypertension in Pre-Elderly (45-59 Years) in The Working Area of The Mano Health Center, East Manggarai District - Marung, Evaristus; Haba Bunga, Eryc Z.; Tira , Deviarbi Sakke (Pergizi Pangan DPD NTT, 2026)
Background : Mano Health Center is one of the health centers in East Manggarai Regency which has the 1st highest number of hypertension cases out of 29 health centers in East Manggarai Regency. Data on hypertension cases at the Mano Community Health Center in 2023 for the 35-72 age group reached 595 cases. Objectives: This study aims to analyze the risk factors for coffee consumption, salt consumption, smoking habits, and alcohol consumption on the incidence of hypertension in the elderly. Methods: This type of research is an analytical survey, with a research design case control. The sample size was 120 people who were divided into 60 case groups and 60 control groups. Data analysis techniques use statistical tests Chi-square. Results: The research results show that there is a relationship between coffee consumption (p-value = 0.006, OR = 3.406), salt consumption (p-value = 0.012, OR = 4.667), smoking (p-value = 0.021, OR = 2.688), and alcohol consumption (p-value = 0.005, OR = 3.143) with the incidence of hypertension in pre-elderly (45-59 years) in the Mano Community Health Center working area, East Manggarai Regency. Conclusions: In conclusion, there is a relationship between coffee consumption, salt consumption, smoking, and alcohol consumption with the incidence of hypertension in the elderly (45-59 years) in the Mano Health Center working area, East Manggarai Regency.